Epidemiological situation on Crimean-Congo Hemorrhagic Fever in the Russian Federation in 2021 - A. S. Volynkina; O. V. Maletskaya; O. N. Skudareva; Ya. V. Lisitskaya; L. I. Shaposhnikova; D. A. Prislegina; E. I. Vasilenko; Yu. M. Tokhov; I. V. Tishchenko; A. V. Kolosov; D. V. Rostovtseva; N. F. Vasilenko; et al. (Проблемы особо опасных инфекций, 2022)
The review presents an analysis of the epidemiological and epizootiological situation on Crimean-Congo hemorrhagic fever (CCHF) in the Russian Federation in 2021. 49 cases of CCHF were detected in 2021, which is 1.53 times higher than in 2020. The mortality rate was 6.1 %. Sporadic cases of CCHF were registered in the Stavropol Territory, Rostov, Volgograd Regions, the Republics of Dagestan and Kalmykia. The incidence rates of CCHF were below the long-term average annual values in the majority of the constituent entities. Epizootiological survey of stationary observation points has revealed that the number of Hyalomma marginatum imago corresponded to the average long-term indicators in 2021, the peak of H. marginatum activity was noted in the II–III decades of May. The proportion of Ixodidae tick pools positive for Crimean-Congo hemorrhagic fever (CCHF) virus markers exceeded the long-term average indexes in a number of regions. On the territory of the natural focus of CCHF, the circulation of the CCHF virus of the genetic lineages “Europe-1” and “Europe-3” was detected in 2021. Based on the analysis of the epidemiological data of the previous year and natural and climatic factors affecting the abundance and vital activity of H. marginatum ticks, risk-based quantitative forecast for the incidence of CCHF in the Stavropol Territory for 2022 has been compiled.